Internal risk limits of dealers and corporate bond market making - Anderson, Christopher S.; McArthur, David C.; Wang, Ke (Journal of Banking & Finance, 2023)
Using novel supervisory data reported in the Volcker metrics, we examine how the internal risk limits of bank-affiliated corporate bond dealers evolved from 2017 to 2020 as indication of capacity constraints on their market making activity. We document that dealers’ internal risk limits came closer to binding during the March 2020 market turmoil. Although dealers eased their limits to accommodate increased liquidity demand, limit adjustments were not enough to offset the increase in risk exposures. We find limit tightness is negatively associated with subsequent inventory growth at dealers’ bond trading desks, especially during the COVID-19 crisis or on days with limit changes. Overall, our results indicate the importance of internal risk limits in driving dealers’ liquidity provision in time of stress.